Psychic and moral exhaustion in primary care workers - Priscilla Brandão Bacci Pegoraro; Rafaela Schaefer; Elma Lourdes Campos Pavone Zoboli (SciELO, 2017)
Abstract OBJECTIVE To report the experience of developing a workshop proposal to assist local managers with the identification, management and prevention of primary care workers' psychic and moral exhaustion. METHOD The workshop was developed through a literature review performed between November 2014 and June 2015. The temporal cut considered studies of the ten previous years. The selection included studies describing collective interventions for situations generating psychic and moral exhaustion, preferably in primary care services. RESULTS Thirty-five articles were analyzed. The workshop provides five meetings with an average duration of one hour. The themes are: awareness; recognizing personal stress; dealing with personal stress; recognizing team stress; and dealing with team stress. The workshop is based on five key principles: detection and coping; attention to interpersonal relationships; communication; self-knowledge and mindfulness. CONCLUSION Psychic and moral exhaustion may reflect negatively on workers' health, the care, and the organization. The proposal of measures to recognize, deal with and prevent psychic and moral exhaustion is relevant and strategic in the constant search for improvement of satisfaction and quality.